2017
DOI: 10.1155/2017/3829472
|View full text |Cite
|
Sign up to set email alerts
|

Biphalin, a Dimeric Enkephalin, Alleviates LPS-Induced Activation in Rat Primary Microglial Cultures in Opioid Receptor-Dependent and Receptor-Independent Manners

Abstract: Neuropathic pain is relatively less responsive to opioids than other types of pain, which is possibly due to a disrupted opioid system partially caused by the profound microglial cell activation that underlines neuroinflammation. We demonstrated that intrathecally injected biphalin, a dimeric enkephalin analog, diminished symptoms of neuropathy in a preclinical model of neuropathic pain in rats (CCI, chronic constriction injury of the sciatic nerve) at day 12 postinjury. Using primary microglial cell cultures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 95 publications
5
18
0
Order By: Relevance
“…Furthermore, in our primary microglial cell cultures, we observed an increase in IBA-1 protein level after LPS stimulation with a significant downregulation of TLR4 protein (Popiolek-Barczyk et al. 2017 ). Therefore, despite the undoubted microglia-TLR4 relationship, the tendency for changes in these two factors (IBA-1 and TLR4) is not necessarily parallel.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, in our primary microglial cell cultures, we observed an increase in IBA-1 protein level after LPS stimulation with a significant downregulation of TLR4 protein (Popiolek-Barczyk et al. 2017 ). Therefore, despite the undoubted microglia-TLR4 relationship, the tendency for changes in these two factors (IBA-1 and TLR4) is not necessarily parallel.…”
Section: Discussionmentioning
confidence: 65%
“…[19; 25-27] The antinociceptive effect of biphalin has been suggested to have a potential role in the treatment of cancer pain, abdominal pain associated with in ammatory bowel disease, and in neuropathic pain via different routes of administration, such as subcutaneous, intravenous, intrathecal, intracerebroventricular, and intraperitoneal. [9,28,29] Furthermore, recent studies have revealed the bene cial role of biphalin on cell viability and neuroprotection against excitotoxic and ischemic damage by inhibiting protein kinase Cdependent sodium potassium-chloride cotransporter expression in focal brain ischemia by activating downstream survival mitogen-activated protein kinases, and by inhibiting reactive oxygen species production in an opioid receptor-dependent manner, which was challenged by naltrexone. [19,25,30] Biphalin also acts as an immunomodulatory agent by stimulating human T cell proliferation, natural killer cell cytotoxicity in vitro, and interleukin-2 production and diminishes pro-and anti-in ammatory factors in lipopolysaccharide-treated microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…NPP is relatively less responsive to opioids than other types of pain. This might be due to the microglial activation caused by severe neuroinflammation, leading to the destruction of the opioid system, which can inhibit the effect of morphine and other opioid drugs on pain control (Popiolek-Barczyk et al, 2017). Microglia communicate with neurons, astrocytes, and other cells, including cells of the immune system, through several receptors and signaling pathways.…”
Section: Microglial Activation: a Bridge Between Npp And Morphine Tolmentioning
confidence: 99%
“…Microglia communicate with neurons, astrocytes, and other cells, including cells of the immune system, through several receptors and signaling pathways. Activated glial cells synthesize and release large amounts of glial mediators such as cytokines, chemokines, growth factors, and proteases, promoting interactions between glial cells and glial cell-neurons (Popiolek-Barczyk and Mika, 2016;Popiolek-Barczyk et al, 2017). Many studies have attempted to determine the roles of these intracellular pathways, which might be involved in the development and maintenance of NPP and morphine tolerance.…”
Section: Microglial Activation: a Bridge Between Npp And Morphine Tolmentioning
confidence: 99%